Pengaruh Religiusitas dan Literasi Zakat terhadap Kepatuhan Membayar Zakat Profesi ASN Kanwil Kementerian Agama Provinsi Jawa Timur - Nikmah, Nur Ziyadatun; Fahrullah, (Universitas Negeri Surabaya, 2024)
Poverty is still a social challenge that must be overcome. Islam has a solution for alleviating poverty through zakat. However, in reality, zakat collection is currently still not optimal. This research aims to determine the influence of religiosity and zakat literacy on compliance with paying zakat by the ASN profession of the Regional Office of the Ministry of Religion of East Java Province. Research data were taken from primary sources through direct distribution of questionnaires and through google forms to respondents. This study uses a quantitative approach with non-probability sampling technique with purposive sampling method. The results of data analysis through SPSS with multiple linear regression show that the religiosity variable has a significant effect on compliance with paying professional zakat.Zakat literacy variable also has a significant effect on compliance to pay professional zakat. Simultaneous testing shows that religiosity and zakat literacy variables have a significant effect on compliance with paying professional zakat. The results of this study also support zakat institutions to improve their programs aimed at increasing religiosity and literacy in society.